Improved Decoding Algorithm of Bit-Interleaved Coded Modulation for LDPC Code - Wang, Ying; Xie, Lei; Chen, Huifang; Wang, Kuang (IEEE transactions on broadcasting, 2010)
Bit-interleaved coded modulation (BICM), which has been proven to be powerful when applied in low-density parity-check (LDPC) sum-product algorithm (SPA) decoder, is a bandwidth efficient coding scheme. However, the BICM-SPA decoder does not take the statistical dependencies between bits from the same L -ary modulated symbol into account so that it cannot converge to the maximum a-posteriori (MAP) decoding algorithm. In this paper, an improved SPA decoding algorithm for the LDPC code, which combines decoding and demodulation, is proposed. The proposed decoding algorithm, referred to as the BICM-ISPA, is based on generalized distributive law and derived from the generalized symbol SPA under certain rational assumptions. And the BICM-ISPA can asymptotically converge to the MAP decoding solution algorithm. Simulation results show that the BICM-ISPA decoder jointly optimizes the decoding error performance and the computational complexity of the LDPC code over the additive white Gaussian noise channel. Compared with the BICM-SPA decoder, the advantage of the BICM-ISPA is quite significant with a large modulation size and in the scenario where Gray mapping cannot be used.